Quality of training in radiation oncology in Germany. Results of a 2006 survey. - Semrau, R; Hansemann, K; Adam, M; Andratschke, N; Brunner, T; Heinzelmann, F; Hildebrandt, G; Vordermark, D; Zips, D (2008)
PURPOSE: To evaluate residents' satisfaction with their training in radiation oncology, the first nationwide survey was done in 2006. Results were presented at the 2006 annual meeting of the German Society of Radiation Oncology (DEGRO). MATERIAL AND METHODS: A questionnaire with 39 questions regarding training in radiation oncology in Germany was developed and sent by e-mail. Questionnaires were returned by mail and analyzed anonymously. RESULTS: 96 questionnaires were received. A total of 88% of respondents are pleased with their decision of training in radiation oncology. Residents are strongly motivated by their interest in oncology. Quality of training is heterogeneous and not optimal. Training in three-dimensional treatment planning, radiochemotherapy and intracavitary brachytherapy is judged adequate, whereas special techniques such as intensity-modulated radiotherapy (IMRT) and permanent prostate implants are not covered by the majority of institutions. Organization of training in the departments is often judged insufficient. CONCLUSION: Radiation oncology is attractive for young doctors. However, training quality for radiation oncologists in Germany was judged to be heterogeneous and needs to be optimized. For this, results of this survey may be helpful. The overall positive judgment may help to attract more students into the field of radiation oncology, an issue that becomes increasingly important given the shortage of doctors and the strong competition with other disciplines. Modern techniques, such as IMRT, need to be integrated into training programs in order to maintain the high standard of radiation oncology in Germany.